2017
DOI: 10.1016/j.juro.2016.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Adrenal Rest Tumors in Boys and Young Adults with Congenital Adrenal Hyperplasia

Abstract: Purpose Testicular adrenal rest tumors (TART) are a well-known complication for males with congenital adrenal hyperplasia (CAH), with potential infertility in adulthood. We assessed the prevalence of TART in infant to young adult males presenting to a CAH Comprehensive Care Center. Materials and Methods 35 males with CAH due to 21-hydroxylase deficiency underwent scrotal ultrasonography (7 males <5 yr, 9 males 5–12 yr, and 19 males >12 yr). There were 32 classical and 3 non-classical CAH. Bone age x-ray (BA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
2
22
0
2
Order By: Relevance
“…Tumors were bilateral in the 9 patients and, in most cases, were small and nonpalpable. These findings are in agreement with the 2009 review by Claahsen-van der Grinten et al [2] and other recent studies that found bilateral tumors in most patients [29, 30]. Only 1 patient with TART was SV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tumors were bilateral in the 9 patients and, in most cases, were small and nonpalpable. These findings are in agreement with the 2009 review by Claahsen-van der Grinten et al [2] and other recent studies that found bilateral tumors in most patients [29, 30]. Only 1 patient with TART was SV.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study by Kim et al [29], a lower prevalence of TART (14%) was described in 35 patients; however, they included 3 patients with nonclassic 21-OHD, in which form TART generally does not occur.…”
Section: Discussionmentioning
confidence: 99%
“…The variability could be attributed to heterogeneity in the selection of patients, age, and the various glucocorticoid treatment regimens. In fact, Kim et al (15) suggested that the prevalence of T-ART is high in young men with CAH, but low in infants or elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Infine, la presenza dei TARTs si associa a un peggior controllo ormonale nei pazienti con CAH, con livelli di ACTH [18], 17-OH-progesterone e androstenedione significativamente più elevati rispetto ai pazienti privi di queste [13,19] manifestazioni. Un inadeguato compenso ormonale, specialmente se protratto nel tempo, può avere notevoli implicazioni cliniche, come età ossea avanzata e bassa statura in pazienti pediatrici [20].…”
Section: Patogenesi E Presentazione Clinicaunclassified